Measuring Systemic Banking Resilience : A Simple Reverse Stress Testing Approach - Feyen, Erik; Mare, Davide Salvatore (World Bank, Washington, DC, 2021)
Reverse stress tests can be a useful tool to evaluate bank resilience to a credit shock, especially in environments where financial data are limited or opaque. This paper develops a simple and transparent country-level banking sector resilience indicator that focuses on tail risks, the Consolidated Distance to Breakpoint. Based on individual bank reverse stress test results, this novel metric quantifies the increase in nonperforming loans needed to deplete capital buffers for a subset of the most fragile banks that collectively represent at least 20 percent of total banking system assets, a level commonly associated with a systemic banking crisis. The paper calculates the Consolidated Distance to Breakpoint using public data for more than 1,500 banks in 59 emerging market and developing economies during the COVID-19 pandemic. The paper explores the value added of this metric in relation to widely used country-level macro-financial and soundness indicators. The results show that the association of the Consolidated Distance to Breakpoint with these macro-financial and financial soundness indicators is limited. This suggests that this new indicator encapsulates complementary information, possibly because aggregate measures may obscure challenges in individual banks. As such, the Consolidated Distance to Breakpoint metric could serve as a useful input to establish a basic understanding of a banking sector’s resilience.